2011
DOI: 10.1159/000324938
|View full text |Cite
|
Sign up to set email alerts
|

Location and Size of Ruptured Intracranial Aneurysm and Serious Clinical Outcomes Early after Subarachnoid Hemorrhage: A Population-Based Study in Australasia

Abstract: Background: It is uncertain whether the location and size of a ruptured intracranial aneurysm (IA) independently influences the outcome of subarachnoid hemorrhage (SAH). Objective: To determine the independent relationship of location and size of a ruptured IA with serious clinical outcomes after SAH in an Australasian population-based study. Methods: From 432 first-ever cases of primary SAH registered prospectively over 12 months in 4 Australasian cities between 1995 and 1998, the demographics, clinical featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 46 publications
0
21
1
Order By: Relevance
“…Review of the abstracts left us with 26 studies for the full-text evaluation. [3][4][5][6]9,10,[18][19][20][22][23][24][25][27][28][29][30][31]33,[35][36][37]39,41 Ten studies were excluded because they did not evaluate aneurysm diameter as a risk factor for rehemorrhage rate. 4,6,9,18,22,24,29,36,39,41 Two other articles were excluded because one was a review and the other was an editorial.…”
Section: Results Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Review of the abstracts left us with 26 studies for the full-text evaluation. [3][4][5][6]9,10,[18][19][20][22][23][24][25][27][28][29][30][31]33,[35][36][37]39,41 Ten studies were excluded because they did not evaluate aneurysm diameter as a risk factor for rehemorrhage rate. 4,6,9,18,22,24,29,36,39,41 Two other articles were excluded because one was a review and the other was an editorial.…”
Section: Results Included Studiesmentioning
confidence: 99%
“…5,19,20,27,28,30,35 In total we identified 9 studies that met our inclusion criteria. 3,10,19,23,27,28,33,37,41 Clinical and/or radiological definitions of rebleeding were given in 8 studies and these are listed in Table 2. Only 1 study reported the median time to rebleeding and the median time to aneurysm repair.…”
Section: Results Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Shiue et al (33) point out that the size of a ruptured aneurysm is an important determinant of outcome in SAH, and should be used as a prognostic parameter in directing management. Yates continuity correction test, p<0.01** in the logistic regression analysis, an aneurysm size above 7 mm was found to be an independent risk factor for mortality but findings were showed the number of aneurysms did not differ significantly in terms of mortality.…”
Section: Localization and Diameter Of Aneurysmmentioning
confidence: 99%